Emotional Odyssey: A Journey through EFL Pre-Service Teachers’ Practicum Experiences - Orlova, Natalia; Kamenická, Jana (Journal of Education Culture and Society, 2024)
Aim. In the realm of English as a Foreign Language (EFL) teacher education, the emotional journey of pre-service teachers remains a relatively unexplored terrain. The present case study addresses this gap by delving into the intricate emotional landscape traversed by pre-service EFL teachers during their initial teaching practicum. Our research objectives are to discern the sources of pre-practicum anxiety among student teachers and compare these with their actual experiences and while-practicum emotions. Methods. Altogether thirteen student teachers in the Czech Republic were interviewed. The data were qualitatively content analysed. Results. The study not only identifies pre-practicum anxieties – including concerns related to rapport, language proficiency, lesson design, and group dynamics, but also scrutinises the transformation of these concerns into nuanced daily classroom management intricacies during the practicum. The research further investigates the positive emotions experienced by pre-service EFL teachers during their practicum, highlighting factors such as a sense of achievement, fruitful interactions, and meaningful teacher-learner relationships. Conclusions. Notably, this study contributes to the understanding of the multifaceted dynamics of pre-service teachers’ professional identities, shedding light on the interplay between anxieties, positive emotions, and the development of teaching identity. The observed shift towards more engaging teaching approaches prompts reflections on emotionally-oriented TEFL, suggesting future research paths and curriculum adjustments